Creating a Marine Defense Technology System in Maintaining Maritime Security - Leo Rasiddin (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Criminal pressure at sea continues to this day, including the arrival of the Covid-19 pandemic which is expected to spread quickly and can be transmitted to members if they are on duty at sea. Corona virus should be one of the country's priorities. The Indonesian state as an area that must be considered in maintaining maritime security in the region is a measure of the independence of the Indonesian state against various forms of maritime criminal pressure. Technology of the Indonesian National Maritime Security Agency in responding to and predicting maritime security threats. The Indonesian Navy must be able to maintain and defend the nation's maritime sovereignty through achieving Indonesia's maritime security. Various activities can be carried out through synergy with maritime safety agencies by combining the strengths and talents of various maritime institutions at sea.